Pengaruh Dosis Pupuk Kandang dan Konsentrasi Plant Growth Promoting Rhizobacteria (PGPR) Terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max L.) - Meisy Ardianti; Maghfoer, Moch Dawam (Produksi Tanaman, 2023)
Soybean is one of the potential food crops that has a high vegetable protein content, which is around 40%. The aim of this study was to obtain an optimal combination of manure dose and PGPR (Plant Growth Promoting Rhizobacteria) concentration on the growth and yield of soybean (Glycine max L.). The study used a randomized block design (RBD) with two factors repeated three times. The first factor is the dose of manure: K1 = 0 tons ha-1, K2 = 10 tons ha-1, and K3 = 20 tons ha-1. The second factor was the concentration of PGPR, namely P0 = 0 ml l-1, P1 = 5 ml l-1, P2 = 10 ml l-1, and P3 = 15 ml l-1. The results showed that there was no interaction between the treatment dose of manure and the PGPR concentration. Separately, the treatment dose of manure and concentration of PGPR had a significant effect on the parameters of plant height, number of leaves, stem diameter, leaf area, plant dry weight, number of productive nodes, number of pods per plant, percent of filled pods, dry seed weight, and weight of 100 seeds. The dose of manure 20 tons ha-1, was able to increase the dry seed yield to 21.42 g plant--1 and 2.91 tons ha-1, and the weight of 100 seeds was 30.49 g plant-1. While the application of PGPR with a concentration of 15 ml l -1 resulted in a dry seed weight of 21.11 g plant-1 and 2.93 tons ha-1 and a weight of 100 seeds of 30.09 g plamt-1, which was higher than without PGPR treatment.